Circulatory amino acid responses to milk consumption in dairy and lactose intolerant individuals - Prodhan, Utpal Kumar; Milan, Amber Marie; Shrestha, Aahana; Vickers, Mark Hedley; Cameron-Smith, David; Barnett, Matthew Philip Greig (European journal of clinical nutrition, 2022)
Background/objectives Self-reported digestive intolerance to dairy foods is common. As dairy can be an important source of dietary protein, this study aimed to identify whether milk protein digestion is compromised in individuals with digestive intolerance. Subjects/methods Adult women ( n = 40) were enroled in this double-blinded, randomised cross-over trial, with digestive symptoms characterised using a lactose challenge and self-reported digestive symptom questionnaire. Participants were classified as either lactose intolerant (LI, n = 10), non-lactose dairy intolerant (NLDI, n = 20) or dairy tolerant (DT, n = 10). In a randomised sequence, participants consumed three different kinds of milk (750 ml); conventional milk (CON), a2 Milk™ (A2M), and lactose-free conventional milk (LF-CON). Circulatory plasma amino acid (AA) concentrations were measured at baseline and every 30 min until 3 h post-ingestion. Results In all participants across all milk types, plasma AA concentrations (AUC 0-180 ) increased after milk ingestion with no significant differences in responses observed between milk types or participants ( P > 0.05), with the exception of the suppressed lysine response in the DT group following A2M ingestion, relative to the other two groups and milk types ( P < 0.05). Conclusion Milk protein digestion, as determined by circulatory AAs, is largely unaffected by dairy- and lactose- intolerances.